In Defence of No Best World. Issue 4 (1st October 2020) - Rubio, Daniel
ABSTRACT: Recent work in the philosophy of religion has resurrected Leibniz's idea that there is a best possible world, perhaps ours. In particular, Klaas Kraay's [2010] construction of a theistic multiverse and Nevin Climenhaga's [2018] argument from infinite value theory are novel defences of a best possible world. I do not think that there is a best world, and I show how both Kraay and Climenhaga may be resisted. First, I argue that Kraay's construction of a theistic multiverse can be resisted from plausible assumptions about set theory. Next, I argue against the value-theoretic assumptions that underlie Climenhaga's argument, and I show how to give an infinite value theory where there is no best world.